The rise and rise of inflation. Issue 2 (16th April 2018) - O'Neill, Rob; Ralph, Jeff; Smith, Paul
Abstract : Where did our current measures of consumer price inflation come from? Who made the important changes that led to the sophisticated methodology we use today, and when were those changes made?Rob O'Neill, Jeff Ralph andPaul Smith explore the history of one of our most important economic indicators Abstract : Where did our current measures of consumer price inflation come from? Who made the important changes that led to the sophisticated methodology we use today, and when were those changes made? Rob O'Neill, Jeff Ralph and Paul Smith explore the history of one of our most important economic indicators.